2023
DOI: 10.1161/circulationaha.122.060860
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation Through Heart-Brain Interaction Initiates Cardiac Inflammation and Hypertrophy During Pressure Overload

Abstract: BACKGROUND: Mechanical stress on the heart, such as high blood pressure, initiates inflammation and causes hypertrophic heart disease. However, the regulatory mechanism of inflammation and its role in the stressed heart remain unclear. IL-1β (interleukin-1β) is a proinflammatory cytokine that causes cardiac hypertrophy and heart failure. Here, we show that NLRP3 (neural signals activate the nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing 3) inflammasome for IL-1β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 53 publications
1
33
0
1
Order By: Relevance
“…GSDMD is a gasdermin family sharing the pore‐forming domains. Despite the necessity of the inflammasome activation in protecting against infections, the system results in unnecessary inflammatory diseases by inflammasome overactivation 27–29 …”
Section: Components and Modulation Of The Panoptosome Complexesmentioning
confidence: 99%
“…GSDMD is a gasdermin family sharing the pore‐forming domains. Despite the necessity of the inflammasome activation in protecting against infections, the system results in unnecessary inflammatory diseases by inflammasome overactivation 27–29 …”
Section: Components and Modulation Of The Panoptosome Complexesmentioning
confidence: 99%
“…Inflammation plays an important role in the development of CVDs. The most current research focused on the NLRP3 inflammasome [77,78] , and other inflammasomes were poorly studied [79] (Table 2).…”
Section: Inflammasomes In Cardiovascular Diseasesmentioning
confidence: 99%
“…Similarly, a recent study, based on NLRP3 gene deletion in male C57Bl/6J mice, revealed that prevention of the early compensatory cardiac hypertrophy response post-TAC accelerated LV dilation and aggravated cardiac dysfunction. 8 Thus, the potential of IL-1β as a therapeutic target to limit HF development in non-ischemic cardiomyopathy currently remains uncertain.…”
Section: Introductionmentioning
confidence: 99%